2001
DOI: 10.1086/319346
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Clostridium tertium Bacteremia in Neutropenic and Nonneutropenic Patients: Review of 32 Cases

Abstract: In the nonneutropenic host, bacteremia due to Clostridium tertium is rare and of unclear significance. We describe a patient in whom presentation with Clostridium tertium bacteremia was the harbinger of Crohn's disease. In order to understand the significance of C. tertium bacteremia in neutropenic and nonneutropenic hosts, we review all 32 cases of C. tertium bacteremia that occurred at Duke University Medical Center from 1992 to 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
96
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(99 citation statements)
references
References 16 publications
0
96
2
1
Order By: Relevance
“…[4] Because of the fact that C. tertium is observed as both gram-positive and -negative bacilli, it can be misidentified as Corynebacterium or Bacillus species; thus, it usually takes considerable time to identify the species using classical bacteriological techniques. [2][3][4][5][6][7][8][9][10] Hence, in our case, we initially misidentified C. tertium as L. grayi.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…[4] Because of the fact that C. tertium is observed as both gram-positive and -negative bacilli, it can be misidentified as Corynebacterium or Bacillus species; thus, it usually takes considerable time to identify the species using classical bacteriological techniques. [2][3][4][5][6][7][8][9][10] Hence, in our case, we initially misidentified C. tertium as L. grayi.…”
Section: Discussionmentioning
confidence: 86%
“…[6,10] However, fatal cases of C. tertium bacteremia have been reported [2,5,8] and we believe that treatment must be initiated upon the identification of the bacterium in blood cultures. To date, although most documented cases have involved neutropenic patients, [2,[5][6][7][9][10][11] cases involving non-neutropenic patients have also been described. [2,4,7,8] Salvador et al [11] reported that C. tertium could be rapidly identified using a novel mass spectrometry technology (matrix assisted laser desorption ionization timeof-flight).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations